Design of half circular wideband antenna for ship radar - Harianto, Bambang Bagus; dwi santoso, Agus (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
The research aims to design a wideband antenna for the ship’s radar. The ship’s radar works on the S-Band range whose wavelengths range from 8 to 15 cm with a frequency of 2-4 GHz, This antenna design uses a new approach involving the use of Defected Ground Structure (DGS) and Defected Microstrip Structure (DMS), which builds on the initial theory. The results of the study obtained a bandwidth value of 1.6 GHz, an impedance antenna value of 49.7 ohms, with a total efficiency of -0.3356 a working frequency range ranging from 1.74 GHz to 3.3 GHz. The radiation pattern obtained the main lobe magnitude value of 3.85 dBi, Main lobe direction of 162.0 deg, angular width (3dB) of 76.7 deg, and side lobe level of -1.1 dB. From the results of working frequency, it is found that the antenna can be used for airborne warning & control (AWACS), remote sensing, WiFi, Bluetooth, mobile communication, XM radio, airport surveillance radar (ASR), radioastronomy, wireless LAN, ZigBee, missile guidance.